Development of an Auxiliary Device for Patellar and Femoral Joint Tangential Axial Radiographic Imaging and a Method for Obtaining an Optimal Radiographic Image Using the Development. (12th October 2022) - Rhee, Do-Byung; Kim, Hee-June; Kwon, Deok-Mun; Kim, Jung-Su; Choi, Hyun-Woo; Kim, Jong-Ki
Abstract : This study evaluated the accuracy of tangential axial radiography of the patellar and femoral joint using an auxiliary device based on three image evaluation criteria, which we named the patellofemoral joint radiography auxiliary device (PJR). To compare the PJR method with conventional radiographic methods, such as Laurin, Merchant, and Settegast, a whole-body phantom (PBU-31) was used and three image evaluation items were set. The radiographic method, the smallest inclination of the patellar and showed the best half lateral image of the patella, is Settegast, and the measurement is 9.40. The second-best PJR measurement is 9.97, and the difference between the two measures is 5.76% (p = 0.001 ). The radiographic method showing the image with the largest distance between the patellar and femoral joint space is PJR which a measurement is 12.35. The second best Merchant measure is 10.55, and the difference between the two measures is 14.54% (p = 0.001 ). The method in which the two bones were well overlapped (i.e., evaluate the distortion of the image by measured as the distance between the femoral trochlear groove and the tibial tuberosity) is the PJR and the measurement is −0.37. The second-best Merchant measure is 3.93, and the difference between the two measures is 91.4% (p = 0.001 ). The Settegast has the image with the smallest inclination of the patella, but the PJR has the image that best describes the patellar–femoral joint and the least distortion of the image. As a result of the comprehensive evaluation, when using PJR, bending the knee by 40° and setting a 140° angle between the long axis of the femur and the long axis of the lower leg were considered to be the most beneficial conditions. Therefore, we propose the use of PJR for tangential axial radiography of the patellar–femoral joint.